Exo/endo stereocontrolled synthesis of spiroindoloindolizidines by using classical and microwave conditions via the 1, 3‐dipolar cycloaddition reaction. (20th May 2020) - Arvinnezhad, Hamid; Ghorbani, Fatemeh; Khosravi, Hormoz; Jadidi, Khosrow; Notash, Behrouz; Naderi, Soheila
Abstract: Using both classical reflux and microwave‐mediated conditions, a series of new spiroindoloindolizidines was synthesized by multicomponent 1, 3‐dipolar cycloaddition of azomethine ylides in unprecedented exo / endo stereocontrolled. Both conditions easily afforded two identical and separable exo / endo diastereomeric ratios of cycloadducts. However, the ratio of two diastereomeric products obtained from conventional conditions was reversed in all examined cases when the reactions were explored under microwave‐mediated conditions. As expected, utilizing the microwave‐assisted conditions produced higher yields and reaction rates compared to classical conditions. The structure and exact stereochemistry of synthesized cycloadducts were determined by applying various 2D‐NMR spectroscopic techniques and single‐crystal X‐ray diffraction. Finally, the mechanism of the reaction has been briefly investigated by using density functional theory (DFT) calculations. Abstract :